Towards Zero Accidents In Construction Projects : Promoting Hirarc As An Effective Tools To Reduce Accidents - Lee, Chia Kuang; Hasahudin, Hassan; Nurhaizan, Mohd Zainudin (2010)
The construction industry contributes significantly to Malaysia’s economy, and yet construction projects are highly risky and hazardous to all walks of life. Accidents occurred in construction site is higher compared to the other industry. The Malaysian government has been giving vigilant attention and constructive efforts to reduce accidents on construction site due to its alarming fatality rates. DOSH particularly has given their highest attention to the implementation of safety management on construction projects, in the hope of achieving a zero accident industry particularly for construction. HIRARC, or known as Hazard Identification, Risk Assessment and Risk Control has been made compulsory for construction projects exceeding over the costs of RM 20 million. This paper has been done to introduce HIRARC, illustrating its concept affiliated with Domino Theory, and exemplified its effectiveness in reducing accidents by comparison based on projects. In the end, the findings show that governance of HIRARC in construction projects is actually effective in managing safety and reducing accidents on construction projects.